Penerapan Model Story-Based Learning untuk Meningkatkan Literasi Multidimensional dan Keterlibatan Emosional Siswa Sekolah Dasar - Srisuk, Prattana; Prastyo, Danang; Tanod, Mareyke Jessy (Bima Journal of Elementary Education, 2024)
This study aims to analyze the effect of implementing the Story-Based Learning (SBL) model on the multidimensional literacy and emotional engagement of elementary school students. The research design employed a quasi-experimental method with a mixed-methods approach. A total of 180 fourth-grade students from three elementary schools were divided into two groups: an experimental group applying SBL and a control group following conventional learning. Quantitative data were collected through pre-test and post-test measures assessing reading, writing, and critical thinking abilities, as well as an emotional engagement questionnaire. In addition, qualitative data were obtained from participatory observations and semi-structured interviews to enrich the understanding of the learning process in the field. The analysis showed that the experimental group experienced a significant increase (p < 0.05) in the multidimensional literacy aspects, particularly in reading (85.4 vs. 78.7), writing (83.1 vs. 75.6), critical thinking (81.5 vs. 73.4), and collaboration and communication (84.0 vs. 77.3). An increase in emotional engagement was also reflected by a rise in motivation scores from 3.2 to 4.0 (on a 1–5 scale), accompanied by a higher level of students’ interest and self-confidence compared to the control group. Classroom observations and interviews indicated that story-based instruction successfully triggered students’ enthusiasm, empathy, and active participation in discussions and expressing opinions. Thus, SBL can be proposed as an effective and holistic learning model for enhancing both the multidimensional literacy and emotional engagement of elementary school students. The practical implications of these findings highlight the importance of teachers’ readiness in selecting relevant stories, designing creative activities, and managing classroom interactions in a communicative manner. Curriculum support and collaboration among stakeholders are also needed to optimize the benefits of SBL, fostering a literate, critical, and empathetic generation.